The Innovation Complex: Cities, Tech, and the New Economy (excerpt) - Sharon Zukin (Journal of Economic Sociology, 2022)
The Innovation Complex presents a broad history of changes occurring worldwide. Focusing on New York City, Sharon Zukin shows a development of a new innovative economy. Each chapter is a study of the production of a particular space with its own embodied cultural forms and economic norms. In these processes, the whole innovation complex, including buildings, districts, and the city acquires scale, form, and sense. To show the scale of the innovation complex and how it works at different levels, the chapters in the book progress from describing smaller spaces to larger ones. The Journal of Economic Sociology publishes the seventh chapter devoted to how educative channels aim to develop the principles of technical and financial meritocracy. The chapter starts at several private elite universities of New York—Cornell, Columbia, and New York University, which use their place within the innovation complex for promoting the institutional agenda of academic capitalism. Then, it considers "Channel for technical talents," the project for creating more inclusive technical labor force, which may involve lower qualified citizens of New York City, including graduates from the New York City University. The last channel covers commercial program schools, such as the General Assembly and Flatiron School, where students pay large fees for 12-week intensive courses to be prepared for work in the technological industry. At the end of the chapter, the author discusses whether the combination of talent, meritocracy and academic capitalism will increase social inequality in the city.